Characteristics of Temperature Field Distribution during Vacuum-Free Electric Arc Synthesis - Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna; Povalyaev P. V. Pavel Vadimovich; Neklya Yu. A. Yuliya Aleksandrovna; Shlyakhov T. S. Timofey Sergeevich; Gerasimov R. D. Roman Dmitrievich; Vlasov A, V. Aleksey Vladimirovich; Pak A. Ya. Aleksandr Yakovlevich (2026, 2026)
Title screen